Prevalence of Domestic Violence Among the Pregnant Women Attending BPKIHS - Regmi, Mohan Chandra; Subedi, Laxmi; Shrestha, Ramesh; Dixit, Baburam; Shrestha, Neha (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out the prevalence of domestic violence in pregnant women attending Antenatal clinics (ANC) of B. P. Koirala Institute of Health Sciences, a tertiary centre in eastern Nepal.Methods: It was a hospital based cross-sectional study done at antenatal clinics of BPKIHS from 14th March 2015 to 30th August 2015. The total number of recruited antenatal patients was 470. Data were collected by face to face interview via pre-tested semi-structured questionnaire. Descriptive and inferential statistics were used for data analysis.Results: The prevalence of domestic violence among pregnant women was 53.2% of which prevalence of physical domestic violence was 9.6%. The most common person inflicting the domestic violence was husband (23.6%). Emotional abuse was the most common form of domestic violence experienced by the pregnant women (26.8%) and threatening for remarriage was most common emotional violence faced (43.2%). As the age of the pregnant women increases, they tend to have more domestic violence.Conclusions: The prevalence of Domestic Violence among pregnant women seemed alarmingly high in our society. Awareness to the family members and strengthening the women empowerment at community level might play a major role for reducing such violence. Pregnancy-related violence is a serious public health issue.